Applications of furrow and micro irrigation in arid and semi-arid regions - Goyal, Megh Raj (Apple Academic Press, 2015)
Applications of Furrow and Micro Irrigation in Arid and Semi-Arid Regions, the fifth volume in the Research Advances in Sustainable Micro Irrigation series, addresses the ever-challenging need for irrigation systems in arid and semi-arid regions of the world, areas that are suffering from severe water shortages. These areas, such as Egypt, Tunisia, most of Africa, and parts of South America, Central America, and Australia, find it a struggle to grow crops sustainably with the water available. This important book emphasizes sustainable agriculture practices to promote increased water usage effi.
Keywords: Microirrigation.; Furrow irrigation.; Arid regions agriculture.; Irrigation.; Soil absorption and adsorption.; elektronické knihy; electronic books